PHOTOSYNTHETIC MICROORGANISMS AS SOURCE OF ANTIOXIDANT AND ANTIBACTERIAL BIOACTIVE COMPOUNDS OF INTEREST IN THE FOOD INDUSTRY - da Silva, Milena Fernandes; Moura, Yanara Alessandra Santana; Porto, Ana Lúcia Figueiredo; Bezerra, Raquel Pedrosa (Revista Valore, 2023)
Bioactive compounds from microalgae and cyanobacteria have been frequently investigated as food preservatives due to their various biotechnological activities. Therefore, this study aimed to evaluate the antimicrobial and antioxidant activities of the aqueous and ethanolic extracts from Dunaliella tertiolecta, Tetradesmus obliquus, and Chlorella vulgaris microalgae and Arthrospira platensis cyanobacteria. The extracts were obtained through the sonication method and the antioxidant activity was determined by ABTS and DPPH methods, whereas antimicrobial activity was evaluated by microdilution assay. In general, ethanolic extracts of all microalgae showed higher antioxidant activity compared to aqueous extracts, especially using ABTS method. All bacteria exhibited higher resistance using the aqueous extracts. Specifically, the gram-negative Pseudomonas aeruginosa was the most susceptible pathogen and was inhibited by all microalgae. The highest antioxidant and antimicrobial activities were obtained by the ethanolic extract from Arthrospira platensis. These data show that ethanolic extract from Arthrospira platensis may be a potential source of antioxidant and antimicrobial compounds with food preservative properties.